2012
DOI: 10.6023/cjoc201206008
|View full text |Cite
|
Sign up to set email alerts
|

Development of Domino Reactions withβ-Enamino Esters as Key Intermediates

Abstract: Domino reactions have attracted much high attention in recent years due to its convergence, productivity, facile execution and generation of highly diverse and complex products from easily available starting materials in a single operation. Addition of primary amines to electron-deficient alkynes could generated reactive enaminone (ester) in mild conditions, which have shown versatile reactivity and have been widely used in domino procedure as key reactive intermediate to develop a number of carbon-carbon bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Over the past decade, nucleophilic phosphine catalyzed reactions have attracted much research effort and have emerged as highly efficient synthetic tools for diverse carbocycles and heterocycles. , In these phosphine catalyzed reactions, in situ generated phosphorus ylides from the addition of triphenylphosphine to electron-deficient alkenes or alkynes are key reactive 1,3-dipoles, which can be captured by suitable substrates to undergo a wide variety of cyclizations and annulations to give versatile carbocyclic and heterocyclic systems. Among these transformations, the electron-deficient alkynoates , and allenonates , are the most common substrates.…”
mentioning
confidence: 99%
“…Over the past decade, nucleophilic phosphine catalyzed reactions have attracted much research effort and have emerged as highly efficient synthetic tools for diverse carbocycles and heterocycles. , In these phosphine catalyzed reactions, in situ generated phosphorus ylides from the addition of triphenylphosphine to electron-deficient alkenes or alkynes are key reactive 1,3-dipoles, which can be captured by suitable substrates to undergo a wide variety of cyclizations and annulations to give versatile carbocyclic and heterocyclic systems. Among these transformations, the electron-deficient alkynoates , and allenonates , are the most common substrates.…”
mentioning
confidence: 99%
“…1 , eq. 2) 14 16 . These kind of active enamines have the similar structural characters to that of the widely employed β- enaminone and β- enmino esters and showed versatile applications in construction of nitrogen-containing heterocycles 17 36 .…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey indicated that the common nitrogen-containing nucleophiles for generation of Huisgen’s 1,4-dipoles are aromatic heterocycles such as N- alkylimidazole, pyridine, quinoline, isoquinoline and primary aromatic amines. In recent years, other nitrogen-containing nucleophiles such as hydrazine and arylhydrazines are also used to generate Huisgen’s 1,4-dipoles in domino reactions [ 19 21 ]. Recently, we and Perumal have demonstrated that the four-component reaction of arylamine, acetylenedicarboxylate, isatin and malononitrile can afford the spiro[indoline-3,4’-pyridine] derivatives in satisfactory yields [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%